The IL-1β Receptor Antagonist SER140 Postpones the Onset of Diabetes in Female Nonobese Diabetic Mice. (3rd February 2016) - Cucak, Helena; Hansen, Gitte; Vrang, Niels; Skarsfeldt, Torben; Steiness, Eva; Jelsing, Jacob
Abstract : The cytokine interleukin-1 β (IL-1 β ) is known to stimulate proinflammatory immune responses and impair β -cell function and viability, all critical events in the pathogenesis of type 1 diabetes (T1D). Here we evaluate the effect of SER140, a small peptide IL-1 β receptor antagonist, on diabetes progression and cellular pancreatic changes in female nonobese diabetic (NOD) mice. Eight weeks of treatment with SER140 reduced the incidence of diabetes by more than 50% compared with vehicle, decreased blood glucose, and increased plasma insulin. Additionally, SER140 changed the endocrine and immune cells dynamics in the NOD mouse pancreas. Together, the data suggest that SER140 treatment postpones the onset of diabetes in female NOD mice by interfering with IL-1 β activated pathways.